Insights on Mycobacterium leprae Efflux Pumps and Their Implications in Drug Resistance and Virulence - Machado, Diana; Lecorche, Emmanuel; Mougari, Faiza; Cambau, Emmanuelle; Viveiros, Miguel (Frontiers in Microbiology, 2018)
Drug resistance in Mycobacterium leprae is assumed to be due to genetic alterations in the drug targets and reduced cell wall permeability. However, as observed in Mycobacterium tuberculosis, drug resistance may also result from the overactivity of efflux systems, which is mostly unexplored. In this perspective, we discuss known efflux pumps involved in M. tuberculosis drug resistance and virulence and investigate similar regions in the genome of M. leprae. In silico analysis reveals that the major M. tuberculosis efflux pumps known to be associated with drug resistance and virulence have been retained during the reductive evolutionary process that M. leprae underwent, e.g., RND superfamily, the ABC transporter BacA, and the MFS P55. However, some are absent (DinF, MATE) while others are derepressed (Mmr, SMR) in M. leprae reflecting the specific environment where M. leprae may live. The occurrence of several multidrug resistance efflux transporters shared between M. leprae and M. tuberculosis reveals potential implications in drug resistance and virulence. The conservation of the described efflux systems in M. leprae upon genome reduction indicates that these systems are potentially required for its intracellular survival and lifestyle. They potentially are involved in M. leprae drug resistance, which could hamper leprosy treatment success. Studying M. leprae efflux pumps as new drug targets is useful for future leprosy therapeutics, enhancing the global efforts to eradicate endemic leprosy and prevent the emergence of drug resistance in afflicted countries.